2005
DOI: 10.1007/bf02731734
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic co-relates of psychiatric disorders

Abstract: Findings suggest a need to educate the community about psychological implications of LBW, large family size and overcrowding in children. Improving maternal education and controlling alcoholism could help in reducing childhood psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 8 publications
8
34
2
Order By: Relevance
“…In line with previous studies,[3715] a higher prevalence rate was seen in 8 to 11 years age group but it was not significant. Factors like increasing burden of studies in schools, emotional disturbances related to early adolescence, or mothers’ perception of any resultant undesired change in behavior as abnormal may be contributing to high prevalence in 8 to 11 years children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies,[3715] a higher prevalence rate was seen in 8 to 11 years age group but it was not significant. Factors like increasing burden of studies in schools, emotional disturbances related to early adolescence, or mothers’ perception of any resultant undesired change in behavior as abnormal may be contributing to high prevalence in 8 to 11 years children.…”
Section: Discussionsupporting
confidence: 91%
“…First, the present study was conducted in Indian setting and community-based studies in India such as Srinath, et al .,[3] Rahi, et al . [7], and Anita, et al . [8] reported prevalence of psychiatric morbidity in children as 12.0% (4-16 years), 16.5% (4-14 years), and 16.5% (6-14 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies by Eapen et al and Rahi M et al, they found alcohol related problems in family and alcoholic fathers to have significant association with psychiatric morbidity in children. 27,28 Substance use in parents predicted delinquency in juveniles, as found in Pittsburgh youth study. 17 Smoking by mother during pregnancy was particularly found to be an important risk factor.…”
Section: Parental Substance Usementioning
confidence: 82%
“…Variables reported to be associated with mental health disorders or symptoms in slum conditions are low level of education, unemployment, and large family size (Silvanus and Subramanian 2012); male gender, lower socioeconomic status, large family, being first-born, having low birth weight, and body mass index (BMI) less than 18.5 (Rahi et al 2005). In a study by Ram et al (2014), family violence and restrictions to independence were associated with mental health problems.…”
Section: Introductionmentioning
confidence: 99%